Evaluation on structural performance of hybrid composite post-tension plate girder through finite element analysis - Al Mustawfi, Sahib; Safiee, Nor Azizi; Abu Bakar, Nabilah; Abd Karim, Izian; Mohd Nasir, Noor Azline (Taylor and Francis Ltd., 2024)
Plate girders are typically formed by the built-up of I-shaped plates. It is vulnerable and weak in resisting buckling. In this study, FE analysis models were developed to evaluate the flexural performance of a hybrid composite post-tension (HCPt) plate girder. The HCPt plate girder is made of double-web and in-fill concrete with pre-stressed tendon to prevent shear web buckling and improve flexural resistance. The sensitivity of design parameters to the performance of the girder was also investigated through a parametric study using four different configurations. The selected parameters are span length, steel grade, concrete grade, and level of pre-stressed force. The statistical analysis was performed using linear multiple regression model to predict the girder’s flexural load and displacement. The results showed that web shear buckling was eliminated for models with in-fill concrete and pre-stressed tendon and failed by bending. Failure of the girder with double web was demonstrated by the combination of bending and web shear buckling. The concrete in-fill prevents the web plate from buckling and the beams generally fail in bending with high ductility. The load capacity of the hybrid composite plate girders with pre-stressing improved by 76% and 44% compared to conventional single-web plate girders and double-web plate girders, respectively. © 2024 Engineers Australia.